Delaying BCG Vaccination from Birth to 10 Weeks of Age May Result in an enhanced Memory CD4 T Cell Response - Kagina, Benjamin M.N.; Bowmaker, Mark; Erasmus, Mzwandile; Walzl, Gerhard (Vaccine, 2009)
In most tuberculosis (TB) endemic countries, bacillus Calmette–Guérin (BCG) is usually given around birth to prevent severe TB in infants. The neonatal immune system is immature. Our hypothesis was that delaying BCG vaccination from birth to 10 weeks of age would enhance the vaccine-induced immune response. In a randomized clinical trial, BCG was administered intradermally either at birth (n=25) or at 10 weeks of age (n=21). Ten weeks after vaccination, and at 1 year of age, vaccine-specific CD4 and CD8 T cell responses were measured with a whole blood intracellular cytokine assay. Infants who received delayed BCG vaccination demonstrated higher frequencies of BCG-specific CD4 T cells, particularly polyfunctional T cells co-expressing IFN-γ, TNF-α and IL-2, and most strikingly at 1 year of age. Delaying BCG vaccination from birth to 10 weeks of age enhances the quantitative and qualitative BCG-specific T cell response, when measured at 1 year of age.
Keywords: BCG; Vaccination; Birth